2010
DOI: 10.1108/09590551011057453
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric cues and their effect on the hedonic retail experience

Abstract: Purpose -The purpose of this paper is to examine the role of atmospherics in the creation of an hedonic retail experience by comparing the perceived differences between a retail environment attempting to provide an hedonic experience and one with a more utilitarian focus. Design/methodology/approach -A qualitative methodology was employed, using protocol analysis and in-depth semi-structured interviews that were conducted with ten participants. Findings -The paper highlights several atmospheric cues and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 40 publications
(39 reference statements)
7
175
0
11
Order By: Relevance
“…Better layout and signage made passengers feel more at ease, but did not result in consistent approach behaviour (Ang, Leong, & Lim, 1997). To some extent, similar findings were found in a qualitative study using a more holistic approach to examine the role of atmospherics in the creation of an hedonic shopping experience (Ballantine, Jack, & Parsons, 2010). Too much or too little space had negative effects, and the perception of space adequacy was also related to levels of clutter in the shop.…”
Section: Layout and Design Factorssupporting
confidence: 62%
“…Better layout and signage made passengers feel more at ease, but did not result in consistent approach behaviour (Ang, Leong, & Lim, 1997). To some extent, similar findings were found in a qualitative study using a more holistic approach to examine the role of atmospherics in the creation of an hedonic shopping experience (Ballantine, Jack, & Parsons, 2010). Too much or too little space had negative effects, and the perception of space adequacy was also related to levels of clutter in the shop.…”
Section: Layout and Design Factorssupporting
confidence: 62%
“…"Commercial and retail" are crucial elements for airports because they stimulate the hedonic experience and excitement of shoppers or passengers (Ballantine, Jack, & Parsons, 2010), especially when airports want to generate a high portion of their revenue from non-aeronautical means (Freathy & O'Connell, 2000;Graham, 2014). The increasing role of passengers in generating revenue urges airports to include retail stores and commercial activities in the airport environment (Brilha, 2008), especially when Kirk (2010 as cited in Livingstone et al, 2012) indicates that passengers spend an average 20% of their overall airport dwell time undertaking necessary activities and 80% of that doing discretionary activities.…”
Section: Service Marketing and Management Perspectivementioning
confidence: 99%
“…9,10 This study draws from previous research by Holbrook and Hirschman 11 that suggested the importance of environmental cues in eliciting positive behavioral responses. It was assumed that positive behavioral response would lead to involvement with malls.…”
Section: Introductionmentioning
confidence: 99%